LB0005 12-week results of a phase 2B dose-ranging study of LY3009104 (INCB028050), an oral JAK1/JAK2 inhibitor, in combination with traditional dmards in patients with rheumatoid arthritis. (23rd January 2014) - Keystone, E.; Taylor, P.; Genovese, M.; Schlichting, D.; Beattie, S.; Gaich, C.; Fidelus Gort, R.; Luchi, M.; Macias, W.L.
Abstract : Background: LY3009104 (LY) is a novel, oral inhibitor of the JAK1/JAK2 signalling pathway known to be important in the pathobiology of rheumatoid arthritis (RA). Objectives: To compare efficacy and safety of LY versus placebo (PBO) in patients (pts) with moderate to severe RA with inadequate response to methotrexate (MTX). Methods: In this Phase 2b, 24-week randomized, double-blind, PBO-controlled study, pts with active RA on stable MTX were randomized 2:1:1:1:1 to receive either PBO or 1 of 4 once-daily LY doses (1, 2, 4, or 8 mg) for 12 weeks. The primary endpoint to evaluate the efficacy of LY was assessed by the combined proportion of pts in the 4-mg and 8-mg dose groups who achieved an ACR20 response compared to PBO over 12 weeks. Results: Of the 301 pts randomized and treated, 76% of the combined 4- and 8-mg (75% of the 4-mg and 78% of the 8-mg dose) groups achieved ACR20 responses compared with 41% of PBO-treated pts (p ≤.001) by the end of 12 weeks. Similarly, greater proportions of pts achieved disease remission as judged by DAS28-CRP in the 4-mg (37%) and 8-mg (22%) dose groups compared to PBO (4%; Table 1 ). Onset of efficacy was rapid for ACR20, ACR50, ACR70, and DAS28-CRP, with statistically significant differences seen from Week 2 onwards. A greater percentage of pts achieved the MCID for the HAQ-DI in the 4-mg (60%) and 8-mg (67%) dose groups compared to PBO (41%) at week 12. Most adverse events (AEs) were mild. A similar rate of infections was observed in PBO (12%) and combined LY (14%) groups representing the most common treatment emergent AE. No deaths or opportunistic infections occurred in the active treatment groups. One pt taking PBO was diagnosed with an opportunistic infection of toxocariasis. Serious AEs were reported in 6 pts (2 in PBO; 3 in 2-mg; 1 in 8-mg). Decreases in hemoglobin, small increases in serum creatinine, and increases in LDL and HDL were seen (Table 2 ). Pt demographics across treatment groups were similar (83% female, mean age 51 years, mean duration of RA 5–7 years, HAQ-DI, 1.02–1.31; DAS28 [ESR], 6.0–6.6). Conclusions: Clinical efficacy of LY against PBO was demonstrated in this Phase 2b study of LY in combination with background MTX in pts with moderate to severe RA. LY was well tolerated. No new safety signals were detected when compared to previously conducted studies with LY. Disclosure of Interest: E. Keystone Grant/Research support from: Abbott Laboratories, Amgen Inc, AstraZeneca Pharmaceuticals LP, Bristol-Myers Squibb, Centocor Inc, F.Hoffman-La Roche Inc, Genzyme Inc, Merck, Novartis Pharmaceuticals, Pfizer Pharmaceuticals, UCB, Consultant for: Abbott Laboratories, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Centocor Inc, F.Hoffman-La Roche Inc, Genentech Inc, Merck, Nycomed, Pfizer Pharmaceuticals, UCB, Speakers Bureau: Abbott Laboratories, Bristol-Myers Squibb Company, F.Hoffman-La Roche Inc, Merck, Pfizer Pharmaceuticals Inc, UCB, Amgen, Janssen Inc., P. Taylor Grant/Research support from: AstraZeneca, Merck, UCB, Celgene, Consultant for: Eli Lilly & Co, Celgene, UCB, Novartis, Merck, NovoNordisk, Abbott, Pfizer, AstraZeneca, Roche, Takeda, M. Genovese Grant/Research support from: Lilly, Pfizer, Rigel, AstraZeneca, Consultant for: Lilly, Pfizer, Rigel, AstraZeneca, Vertex, Biogen-Idec, Astellas, D. Schlichting Shareholder of: Eli Lilly & Co, Employee of: Eli Lilly & Co, S. Beattie Shareholder of: Eli Lilly & Co, Employee of: Eli Lilly & Co, C. Gaich Shareholder of: Eli Lilly & Co, Employee of: Eli Lilly & Co, R. Fidelus Gort Employee of: Incyte Corp., M. Luchi Shareholder of: Incyte Corp., Employee of: Incyte Corp., W. Macias Shareholder of: Eli Lilly & Co, Employee of: Eli Lilly & Co